Unemployment and the rising number of non-workers in urban China: Causes and distributional consequences - Björn Gustafsson; Sai Ding (The University of Western Ontario, CIBC Centre for Human Capital and Productivity, 2011)
Chapter from: 'Rising Inequality in China: Challenge to a Harmonious Society', edited by Shi Li, Hiroshi Sato and Terry Sicular.
Keywords: 330; Arbeitsmarkt; Arbeitslosigkeit; Einkommensverteilung; Ballungsraum; China